Immunohistopathology and Steroid Profiles Associated With Biochemical Outcomes After Adrenalectomy for Unilateral Primary Aldosteronism. Issue 3 (September 2018) - Meyer, Lucie S.; Wang, Xiao; Sušnik, Eva; Burrello, Jacopo; Burrello, Alessio; Castellano, Isabella; Eisenhofer, Graeme; Fallo, Francesco; Kline, Gregory A.; Knösel, Thomas; Kocjan, Tomaz; Lenders, Jacques W.M.; et al.
Abstract : Unilateral primary aldosteronism (PA) is the most common surgically curable form of hypertension that must be accurately differentiated from bilateral PA for therapeutic management (surgical versus medical). Adrenalectomy results in biochemical cure (complete biochemical success) in almost all patients diagnosed with unilateral PA; the remaining patients with partial or absent biochemical success comprise those with persisting aldosteronism who were misdiagnosed as unilateral PA preoperatively. To identify determinants of postsurgical biochemical outcomes, we compared the adrenal histopathology and the peripheral venous steroid profiles of patients with partial and absent or complete biochemical success after adrenalectomy for unilateral PA. A large multicenter cohort of adrenals from patients with absent and partial biochemical success (n=43) displayed a higher prevalence of hyperplasia (49% versus 21%; P =0.004) and a lower prevalence of solitary functional adenoma (44% versus 79%; P <0.001) compared with adrenals from age- and sex-matched patients with PA with complete biochemical success (n=52). We measured the peripheral plasma steroid concentrations in a subgroup of these patients (n=43) and in a group of patients with bilateral PA (n=27). Steroid profiling was associated with histopathologic phenotypes (solitary functional adenoma, hyperplasia, and aldosterone-producing cell clusters) and classified patients according to biochemical outcome or diagnosis of bilateral PA. If validated, peripheral venous steroid profiling may be a useful tool to guide the decision to perform surgery based on expectations of biochemical outcome after the procedure. Abstract : Supplemental Digital Content is available in the text.